Global temporal trends and projections of hepatitis B-related cirrhosis among adolescents and young adults from 1990 to 2035: an analysis based on the global burden of disease study 2021 - He, Quanwei; Chang, Xiujuan; Xu, Ran; Han, Wei; Wang, Sihao; Gong, Shujuan; Huang, Jiagan; Liu, Jiangtao; Zhang, Rugang; Yang, Yongping (Frontiers in Public Health, 2025)
BackgroundChronic hepatitis B and cirrhosis pose significant global health threats. Few studies have explored the disease burden and mortality trend of cirrhosis caused by hepatitis B virus infection among adolescents and young adults (AYAs, aged 15–39 years). This study aimed to assess the disease burden and trends.MethodsPublicly available data were obtained from the 2021 GBD database. The rates of incidence, mortality, and disability-adjusted life years were calculated at the global, regional, and national levels. Temporal trends were assessed using joinpoint regression analysis, while the Bayesian age-period-cohort model was used to predict future trends.ResultsFrom 1990 to 2021, the global incidence rate of hepatitis B-related cirrhosis decreased from 111.33 (95% uncertainty interval: 89.18 to 134.98) to 67.75 (54.06 to 82.71) per 100,000 with an average annual percentage change of −1.58 (95% confidence interval: −1.66 to −1.51, p < 0.001). However, between 1990 and 2021, the incidence numbers in the 30–34 and 35–39 age groups increased by 23.75 and 21.24%, respectively. The number of deaths in low and low-middle Socio-demographic Index (SDI) areas increased by 79.51 and 20.62%, respectively. Moreover, it is predicted that the numbers of incidences and deaths will continue to rise in areas with low SDI. At the regional level, Central Sub-Saharan Africa had the highest incidence and mortality rates. In 2021, Somalia and the Democratic Republic of Congo had the highest incidence rates, whereas Kiribati and Cambodia had the highest mortality rates.ConclusionThe overall burden of hepatitis B-related cirrhosis among AYAs has decreased over the past three decades. Nevertheless, there was a slight increase in the incidence number among individuals aged 30–39 years. The substantial burden and predicted rise in the numbers of incidences and deaths in low SDI areas underscore the need for sustained and targeted public health interventions.